Perancangan Interior â€œRumah Anjingâ€ bagi Pecinta Anjing Trah di Surabaya - Tedja, Madeline Kartika; Padmanaba, Cok Gede; Mulyono, Grace (Intra, 2016)
Dogs are animal that have a very close relationship with human. Their loyalty and devotion is very similar with human concept about love and friendship. Thatâ€™s why a lot of people make dogs their bestfriends or even treat them like their own family member. Interior design of â€œRumah Anjingâ€ is a design that can fullfill and satisfy the needs of all dog lovers, especially in Surabaya. The facilities that are provided are pet shop, grooming and salon area, clinic area, dog training area, dog day care area, and cafe. By using a design concept that can â€œpamperâ€ so as to facilitate all visitorâ€™s activities, providing a cozy and warm atmosphere using a natural materials such as wood, stone, and greenery accent in the room. In this design, we use collecting data method such as literature study, observation and survey. Interior design of â€œRumah Anjingâ€ is believed to fulfill the necessary requirements of dog lovers, as well as providing a new and exciting atmosphere and experience for people in Surabaya.